MALGUDI DAYS IN THE INDONESIAN CLASSROOM: FOSTERING LITERACY, CRITICAL THINKING, AND GLOBAL CITIZENSHIP FOR A COMPETITIVE WORKFORCE (ALIGNED WITH SDG 4) - Priyanka Marwaha; Ramnita Saini Sharda (Cirebon International Conference on Education and Economics Proceeding, 2024)
In today’s interconnected world, fostering a well-rounded workforce equipped with literacy, critical thinking skills, and a sense of global citizenship is paramount. This research explores the potential of R.K. Narayan’s Malgudi Days to achieve this objective within Indonesian classrooms, aligning with Sustainable Development Goal 4 (SDG 4) of ensuring quality education. Malgudi Days, set in the fictional Indian town of Malgudi, offers relatable characters and themes that transcend geographical boundaries. This study examines how these stories can enhance Indonesian students’ literacy skills through engaging narratives and diverse writing styles. Beyond language mechanics, analysing characters’ struggles and societal issues encourages critical thinking about universal human experiences and ethical dilemmas, fostering intercultural understanding and empathy. Additionally, the research highlights how Malgudi Days can cultivate a sense of global citizenship. By exploring lives in a different cultural context, students develop a broader worldview, learning to identify commonalities and celebrate differences, thus preparing them for effective communication and collaboration in a globalised workforce. This study contributes to improving educational outcomes in Indonesia by demonstrating the power of literature to nurture well-rounded individuals. By integrating Malgudi Days into the curriculum, Indonesian classrooms can empower students with the critical thinking, literacy, and global citizenship skills necessary to thrive in the 21st century.